Effect of Cnidoscolus aconitifolius (Family Euphorbiaceae) Aqueous Leaf Extract on Some Antioxidant Enzymes and Haematological Parameters of High Fat Diet and Streptozotocin Induced Diabetic Wistar Albino Rats - EA Obichi; CC Monago; DC Belonwu (Journal of Applied Sciences and Environmental Management)
This study was carried out to evaluate the oxidative and haematologic effects of aqueous extract of Cnidoscolus aconitifolius (CA) in high fat diet (HFD) and streptozotocin (STZ) induced diabetes in Wistar albino rats. Diabetes was induced by feeding the rats with HFD that consisted of 20% sucrose and 20% lard for 4 weeks, followed by a single dose intraperitoneal injection of STZ (40mg/kg body weight (BW)). The aqueous leaf extract of CA was administered orally and daily at 400, 600 and 800mg/kg BW from 7days after induction of diabetes and lasted for 12 weeks, while the normal control and diabetic control rats received regular diet and HFD respectively. Metformin (50mg/kg BW) was used as a standard antidiabetic drug. The animals were anaesthetized and sacrificed to obtain blood by cardiac puncture. Preliminary phytochemical analysis of CA showed the content of tannins (5.72±0.00), saponins (12.49±0.021), alkaloids (17.45 ±0.65), flavonoids  (23.72 ±0.02), cyanogenic glycosides (0.75 ±0.10) and phytate (1.97 ±0.06). The six vitamins analysed, showed the concentration of vitamin A (5.24mg/kg), vitamin B3 (1.40mg/kg), vitamin B6 (37.23mg/kg), vitamin B12 (15.98mg/kg), vitamin C (382.00mg/kg) and vitamin E (18.28mg/kg). There was significantly  (p<0.05) reduced activity of catalase (CAT), significantly (p<0.05) increased level of TBARS, and non significantly (p>0.05) reduced activity of superoxide  dismutase (SOD), Packed Cell Volume (PCV) and haemoglobin (Hb) concentration in HFD/STZ induced diabetic rats. CA significantly (p<0.05) increased the SOD and CAT activities, PCV, and Hb concentrations of the treated diabetic rats (TDR) while the TBARS was significantly (p<0.05) decreased compared to the diabetic control (DC). Our findings suggest that CA exhibited reversal effects on these selected oxidative and haematologic markers in rats which were previously damaged by HFD and STZ.